1991
DOI: 10.1144/gsjgs.148.4.0703
|View full text |Cite
|
Sign up to set email alerts
|

Resetting of Rb–Sr whole-rock ages during Acadian low-grade metamorphism in North Wales

Abstract: Ordovician volcanic rocks and associated sub-volcanic intrusions in North Wales give Devonian, metamorphic Rb-Sr whole-rock ages. Isotopic resetting is not confined to acid volcanic rocks. Three intrusions preserve Ordovician ages. The closed system resetting is not directly related to metamorphic grade, but appears to correlate with the extent to which the secondary metamorphic mineral assemblage is developed. Rocks giving Devonian ages have a well developed secondary mineralogy whereas those retaining Ordovi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
25
0

Year Published

1992
1992
1999
1999

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(26 citation statements)
references
References 25 publications
1
25
0
Order By: Relevance
“…The modeling is developed for the Cadair Idris region of central Wales for which a well-documented stratigraphy and metamorphic development has been established. It is the region where the highest metamorphic grade can be clearly defined with metabasites having a low-greenschist facies assemblage of actinolite+epidote (Figure 1) to a low-grade metamorphic assemblage, an age of 399 ñ 9 Ma was proposed for the metamorphism, an age younger than that of cleavage formation [Evans, 1991]. These age data, in fact, showed a spread from 507 to 325 Ma that was attributed to the intensity of recrystallization in individual samples, as a response to the variable availability of water during the metamorphism [Evans, 1991].…”
Section: Stratigraphic and Sedimentological Constraintsmentioning
confidence: 99%
“…The modeling is developed for the Cadair Idris region of central Wales for which a well-documented stratigraphy and metamorphic development has been established. It is the region where the highest metamorphic grade can be clearly defined with metabasites having a low-greenschist facies assemblage of actinolite+epidote (Figure 1) to a low-grade metamorphic assemblage, an age of 399 ñ 9 Ma was proposed for the metamorphism, an age younger than that of cleavage formation [Evans, 1991]. These age data, in fact, showed a spread from 507 to 325 Ma that was attributed to the intensity of recrystallization in individual samples, as a response to the variable availability of water during the metamorphism [Evans, 1991].…”
Section: Stratigraphic and Sedimentological Constraintsmentioning
confidence: 99%
“…Rb-Sr isotope systems of the igneous rocks of North Wales were disturbed during Acadian deformation (about 400 Ma). However, this disturbance was a closed system redistribution of Rb and Sr (Evans 1991) and it is therefore possible to back-calculate the data to Ashgill times and retain realistic estimates of the Sr isotopic composition of the rocks at that time. The Sr isotopic compositions are available for many of the possible source rocks as well as the samples in this study and help to give a clearer presentation of the groups of data under discussion and so it is included as a discriminant in this study although it is much more easily disturbed, and therefore less reliable, than the S M d isotope systems.…”
Section: Presentation Of Datamentioning
confidence: 99%
“…Mixing of materials during transport will produce an average figure for all the rocks contributing to the sediment flux (McCulloch & Wasserburg 1978) weighted according to the REE budget of the various source lithologies. Isotopes of Rb and Sr behave in a similar way, and experience has shown that though they are more mobile, their redistribution is often in a closed system (Evans 1991). They can therefore be used, with caution, as a discriminant along with Sm and Nd (Leng & Evans 1994).…”
mentioning
confidence: 99%
“…The use of these epsilon plots in provenance studies has the great advantage of distinguishing between sediments produced by the erosion of sourcelands comprising rock types of similar composition but different ages. Isotope studies are able to distinguish between different generations of volcanic material, for example, and thus between otherwise identical rock types (Evans 1989 Mearns et al 1989). Outside this range specific sources are dominant, so for example, anomalously young TDM ages often identify additions from more juvenile igneous source rocks (Thorogood 1990).…”
mentioning
confidence: 99%
See 1 more Smart Citation